Inhibiting PI3K-AKT-mTOR signaling in multiple myeloma-associated mesenchymal stem cells impedes the proliferation of multiple myeloma cells - Heinemann, Luca; Möllers, Klara Maria; Ahmed, Helal Mohammed Mohammed; Wei, Lanying; Sun, Kaiyan; Nimmagadda, Subbaiah Chary; Frank, Daria; Baumann, Anja; Poos, Alexandra; Dugas, Martin; Varghese, Julian; Raab, Marc-Steffen; et al. (Frontiers in oncology, 2022)
The microenvironment of cancer cells is receiving increasing attention as an important factor influencing the progression and prognosis of tumor diseases. In multiple myeloma (MM), a hematological cancer of plasma cells, mesenchymal stem cells (MSCs) represent an integral part of the bone marrow niche and tumor microenvironment. It has been described that MM cells alter MSCs in a way that MM-associated MSCs promote the proliferation and survival of MM cells. Yet, our understanding of the molecular mechanisms governing the interaction between MM cells and MSCs and whether this can be targeted for therapeutic interventions is limited. To identify potential molecular targets, we examined MSCs by RNA sequencing and Western blot analysis. We report that MSCs from MM patients with active disease (MM-Act-MSCs) show a distinct gene expression profile as compared with MSCs from patients with other (non-) malignant diseases (CTR-MSCs). Of note, we detected a significant enrichment of the PI3K-AKT-mTOR hallmark gene set in MM-Act-MSCs and further confirmed the increased levels of related proteins in these MSCs. Pictilisib, a pan-PI3K inhibitor, selectively reduced the proliferation of MM-Act-MSCs as compared with CTR-MSCs. Furthermore, pictilisib treatment impaired the MM-promoting function of MM-Act-MSCs. Our data thus provide a deeper insight into the molecular signature and function of MSCs associated with MM and show that targeting PI3K-AKT-mTOR signaling in MSCs may represent an additional therapeutic pathway in the treatment of MM patients.
Gesehen am 02.08.2022